Efektivitas Implementasi Aplikasi Sakti Dalam mendukung Digitalisasi Penyusunan Laporan Keuangan - Fatharani, Fatharani; Fachruzaman, Fachruzaman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
Digital transformation in public financial governance is an essential part of bureaucratic reform aimed at enhancing transparency and accountability. This study aims to analyze the effectiveness of the implementation of the SAKTI application in supporting the digitalization of financial statement preparation at the Regional Office of the National Land Agency (BPN) of Bengkulu Province. The research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews with eleven informants, including operators, validators, and approvers, and were strengthened by documentation and triangulation techniques to ensure data validity. The results indicate that the implementation of SAKTI is effective in improving the efficiency of reporting processes and the accuracy of financial records through automatic validation that minimizes input errors. Systemically, the application integrates all stages of financial management, from planning to accountability, within a single system equipped with a strong audit trail. Employees perceive this digitalization as a shift toward greater personal responsibility and increased compliance with procedures. Although technical issues such as network disruptions and centralized system maintenance were encountered, these were temporary and did not significantly hinder the reporting process. Overall, SAKTI has successfully strengthened the principles of good governance in technical government institutions.